Analysis Of Construction Management On The Ashley Hotel Central Jakarta Development Project - Aghniya, Shilvy; Anwar, Saihul (Journal of Green Science and Technology, 2019)
Construction Management is the process of implementing management functions (Planning, Organizing, Actuating and Controlling) systematically on a project by using existing resources effectively and efficiently in order to achieve project objectives optimally.Analysis of Construction Management on the Ashley Hotel Central Jakarta Development Project isstartingfromtheanalysisofimplementationmethod,thecalculationoftheworkvolume,thecalculation of the needs of labor, material, and equipment, the calculation of the budget plan, and the time and cost control project with Barchart, S-Curve and Critical Path Method(CPM).Based on the analysis that has been done with Barchart, S-Curve and CPM, the construction of Ashley Hotel takes 69 weeks with an estimated cost of Rp. 39.091.299.600,00.Keyword : Construction Management, Barchart, S-Curve, CPM (Critical Path Method).